The significance of wrist immobilization for endoscopic carpal tunnel release - Zhang, Fei; Jiang, Hong; Lu, Zhenfeng; Yang, Haoyu; Zhang, Qian; Mi, Jingyi; Rui, Yongjun; Zhao, Gang (Frontiers in Neurology, 2023)
Background Over the years, endoscopic carpal tunnel release (ECTR) has gained significant interest as an alternative to surgery. However, no consensus has been reached on the necessity of postoperative wrist immobilization. This study aims to compare the outcomes of wrist immobilization for a period of 2 weeks to immediate wrist mobilization after ECTR. Methods A total of 24 patients with idiopathic carpal tunnel syndrome undergoing dual-portal ECTR from May 2020 to Feb 2022 were enrolled and randomly divided into two groups postoperatively. In one group, patients wore a wrist splint for 2 weeks. In another group, wrist mobilization was allowed immediately after surgery. The two-point discrimination test (2PD test); the Semmes–Weinstein monofilament test (SWM test); the occurrence of pillar pain, digital and wrist range of motion (ROM); grip and pinch strength; the visual analog score (VAS), the Boston Carpal Tunnel Questionnaire (BCTQ) score; the Disabilities of the Arm, Shoulder, and Hand (DASH) score; and complications were evaluated at 2 weeks and 1, 2, 3, and 6 months after the surgery. Results All 24 subjects finished this study with no dropouts. During the early follow-up, patients with wrist immobilization demonstrated lower VAS scores, lower occurrence of pillar pain, and higher grip and pinch strength compared with the immediate mobilization group. No significant difference was obtained between these two groups in terms of the 2PD test, the SWM test, digital and wrist ROM, BCTQ, and the DASH score. In total, two patients without splints reported transient scar discomfort. No one complained of neurapraxia, injury of the flexor tendon, median nerve, and major artery. At the final follow-up, no significant difference was found in any parameters between both groups. The local scar discomfort mentioned above disappeared and left no serious sequela. Conclusion Wrist immobilization during the early postoperative period demonstrated significant pain alleviation along with stronger grip and pinch strength. However, wrist immobilization yielded no obvious superiority regarding clinical outcomes at the final follow-up.